1)(-6;8)
2)(9;-1)
Пошаговое объяснение:
1)
умножаем верхнее уравнение на -1:
-2x-7y+44+2x-3y=0-36
-7y-3y=-36-44
-10y=-80
y=80/10=8
2x=3y-36=8*3-36=-12
x=-6
2)
умножаем нижнее уравнение на 2
x-8y-17+6x+8y-46=0+0
7x=63
x=63/7=9
4y=23-3x=23-27=-4
y=-1
надеюсь правильно
1)(-6;8)
2)(9;-1)
Пошаговое объяснение:
1)
умножаем верхнее уравнение на -1:
-2x-7y+44+2x-3y=0-36
-7y-3y=-36-44
-10y=-80
y=80/10=8
2x=3y-36=8*3-36=-12
x=-6
2)![\left \{ {x-8y-17=0} \atop {3x+4y-23=0}} \right.](/tpl/images/1857/2825/fb02e.png)
умножаем нижнее уравнение на 2
x-8y-17+6x+8y-46=0+0
7x=63
x=63/7=9
4y=23-3x=23-27=-4
y=-1
надеюсь правильно